Development of Sīroh An-Nabawiyyah Learning Media in Fiqh Siroh Ramadhan Al-Buthi Through the Concept of NPT (Narative, Pedagological, and Theological) - Udin Supriadi; Mohammad Rindu Fajar Islamy (UNIVERSITAS PAKUAN, 2023)
This study aims to develop the Sīroh An-Nabawiyyah Learning Media Through the Concept of Fiqh Sīroh Ramadhan Al-Buthi based on NPT (narrative, pedagogical, and theological) with the support of historical visualization. In the dimension of modernity, globalization and technological acceleration have an effect on reducing the moral morality of the younger generation. According to the contemporary Muslim scholar Prof. Dr Muhammad Sa'id Ramadhan Al-Buthi in his work Fiqh As-Sīroh recommends that the younger generation must be friends with the figure of Rasulullah SAW as an ideal role model in all aspects. Every event that happened to Rasulullah, according to Al-Buthi has pedagogical values that can be implemented in the life of a Muslim, thus giving birth to a young generation who is religious and religious. In line with Al-Buthi, Prof. Dr. Ali Jum'ah, a senior scholar of Al-Azhar Egypt, recommended that the younger generation be trained to build the paradigm of